Meningkatkan Minat Belajar Siswa Bernalar Kritis Model PBLMateri Panggilan Hidup Berkeluarga Fase F SMKN 1 Tamiang Layang - Mariantoni Mariantoni (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The low interest of students in thematic learning is because students do not know how to solve problems or issues related to learning material. The purpose of this research is to find out whether the problem-based learning model can increase students' interest and learning outcomes. The population in this study were twelve grade students at SMK N 1 Tamiang Layang with a total of 18 students. The type of research used was classroom action research. Data collection techniques used are questionnaires and tests. The data used is in the form of quantitative data in the form of interest in learning questionnaire results and students' written test results. Data analysis technique uses descriptive qualitative. Based on the research conducted, it was found that interest in learning in cycle I with a low category reached 17%, medium 61% and high reached 0% increased in cycle II with a low category reaching 0%, medium 11% and high reaching 89%. Likewise, the learning outcomes in the first cycle reached 67% incomplete and 33% of the total students passed the KKM (≥75) incomplete and reached 11% incomplete and reached 89% complete in cycle II. Thus it can be concluded that the application of the Problem Based Learning (PBL) model is effective in increasing interest in learning and student learning outcomes.